Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1093/braincomms/fcac006
|View full text |Cite
|
Sign up to set email alerts
|

Hyperexcitable superior colliculus and fatal brainstem spreading depolarization in a model of Sudden Unexpected Death in Epilepsy

Abstract: Cardiorespiratory arrest and death in mouse models of Sudden Unexpected Death in Epilepsy occur when spreading depolarization is triggered by cortical seizures and then propagates to the brainstem. However, the critical brain regions and the specific changes required to allow spreading depolarization to propagate to the brainstem under the relatively rare circumstances leading to a fatal seizure are unknown. We previously found that following cortical seizure-inducing electrical stimulation, spreading depolari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Brainstem spreading depolarization (SD) has been reported to be associated with SUDEP pathophysiology in some transgenic mouse models using anesthetic preparations (Aiba and Noebels, 2015; Aiba et al, 2016; Cain et al, 2022). Further, several rodent studies using general anesthesia have reported an association between brain hypoxia and SD (Funke et al, 2009; Richter et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brainstem spreading depolarization (SD) has been reported to be associated with SUDEP pathophysiology in some transgenic mouse models using anesthetic preparations (Aiba and Noebels, 2015; Aiba et al, 2016; Cain et al, 2022). Further, several rodent studies using general anesthesia have reported an association between brain hypoxia and SD (Funke et al, 2009; Richter et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Aiba and Noebels, 2015;Aiba et al, 2016;Cain et al, 2022). Further, several rodent studies using general anesthesia have reported an association between brain hypoxia and SD(Funke et al, 2009;Richter et al, 2010).…”
mentioning
confidence: 97%
“…It has long been known to underlie pathophysiology in migraine and has more recently been implicated in traumatic brain injury, epilepsy and SUDEP [81]. Recent studies in a hyperexcitable mouse model demonstrate that when SD reaches superior colliculus, it is more likely to be fatal [86,87 ▪ ,88]. In certain syndromic epilepsies, ion channel mutations could also be present in key control regions and directly impair cardiorespiratory function in this manner [49].…”
Section: Mechanisms For Sudden Unexpected Death In Epilepsymentioning
confidence: 99%
“…Similar results were also observed in mice expressing a Ca v 2.1 gain of function mutation associated with familial hemiplegic migraine type 1 10.3389/fncir.2022.1033756 (Cacna1a S218L/+ ; Jansen et al, 2019) and mice expressing a ryanodine receptor-2 gain of function mutation associated with catecholaminergic polymorphic ventricular tachycardia (Aiba et al, 2016). Also, in Cacna1a S218L/+ mice the superior colliculus, a midbrain structure that receives input from both the cortex and brainstem, was particularly effective at propagating seizureinduced SD to the brainstem (Cain et al, 2022), suggesting anatomical connectivity may facilitate SD.…”
Section: Spreading Depolarizationmentioning
confidence: 99%